Dose-response relationship between the number of sprint repetitions and physiological and performance adaptations in team-sport athletes - Yamagishi, T.; Hagiwara, M.; Ando, R.; Shiraki, S.; Henderson, F.; Yamashita, D. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Repeated sprint training (RST) consisting of short (* 10 s) sprints interspersed with brief (* 60 s) rest periods is known to bring about various training benefits including explosive, intermittent and endurance performances (1). Since RST imposes physical and physiological demands similar to those in intermittent sports (e.g., team, racket, and combat sports), this training modality is popular among various athletes. However, the number of sprint repetitions to optimise training adaptations remains unknown. Considering that athletes often face congested schedules (e.g., sport training, competitions, work/school), establishing cost-effective ways to bring about training benefits is highly desirable. Thus, this study sought to determine the dose-response relationship between the number of sprint repetitions and physiological and performance adaptations in team-sport athletes. METHODS: Nineteen male university basketball players (20 ± 1 yrs, 176 ± 7 cm, 73 ± 9 kg, maximal oxygen uptake [VO2max]: 56.0 ± 4.6 ml/kg/min) were allocated to one of three training groups (matched for baseline physiological and performance values); high-volume group (HG, n = 7), medium-volume group (MG, n = 7) and low-volume group (LG, n = 5). All groups performed 6 sessions of RST consisting of 6-s cycle sprints interspersed with 30-s recovery over 2 to 4 weeks. In each session, HG, MG and LG completed 15-24 sprints (112 in total), 10-18 sprints (80 in total) and 5-12 sprints (48 in total), respectively. Before and after the intervention, 6-s cycle test-derived peak (PP) and average (AP) power, and maximal incremental power (MIP) and VO2max achieved in an incremental cycle test were determined. RESULTS: A one-way analysis of variance with Gabriel post hoc test revealed a main effect of group (p < .05) in % change of PP (HG: 6.8 ± 6.5%; MG: 14.7 ± 8.9%; LG: 3.5 ± 2.9%) and MG showed significantly greater improvements than LG (p < .05). A similar result was observed in % change of AP where a main effect nearly reached significance (HG: 10.3 ± 7.0%; MG: 15.9 ± 7.6%; LG: 5.8 ± 3.6%, p = .05), and MG tended to show greater improvements than LG (p = .05). There were no group differences in % changes of MIP (HG: 4.4 ± 3.3%; MG: 2.4 ± 3.6%; LG: 3.9 ± 3.8%) and VO2max (HG: 4.2 ± 4.4%; MG: 2.0 ± 4.8%; LG: 2.7 ± 8.8%). CONCLUSION: Our findings suggest that medium training volume is most effective in improving short-term power (PP and AP), whereas endurance adaptations (MIP and VO2max) are not dependent on training volume which is partially in line with previous findings in non-athletes (2).